Hľadanie identity ECAV na Slovensku vo vzťahu k transrodovým ľuďom - Ľubomír Batka (Teologická Reflexe)
In the Evangelical Church of the Augsburg Confession in Slovakia (ECAV), the initially emotional rejection of transgenderism has been transformed into theological rationalization without dialogue with experts and transgender people. The term “gender ideology” is used imprecisely, serves to reject liberal attitudes towards LGBTIQ+ rights, and is based on conservative theological beliefs without a deeper analysis of gender studies. ECAV perceives gender ideology as a construction denying biological differences and refers to a superficial critique of radical feminism and transgenderism. ECAV’s position presents a conservative theological view that considers transidentity sinful and prohibits transgender people from spiritual service, thereby creating discriminatory conditions. It relies on a “theocentric” interpretation of the Bible and tradition, ignores scientific knowledge about gender identity, and binds the conscience of Evangelicals to strict adherence to sexual moral standards. It emphasizes a binary understanding of gender and the order of creation, linking transgenderism to original sin without offering real pastoral or social support. This stance legitimizes the stigmatization of transgender people and raises the question of whether it truly reflects an evangelical identity or is rather a tool for controlling the conscience and privacy of believers.